MORPHOLOGICAL VARIATION OF THE THREE SPECIES FRUIT BAT GENUS MEGAEROPS FROM INDONESIA WITH ITS NEW DISTRIBUTION RECORD - Maharadatunkamsi Maharadatunkamsi; Ibnu Maryanto (Treubia, 2002)
Morphological variation in the fruit bat Megaerops spp. from five islands in Indonesia were examined. Univariate and multivariate statistical analyses based on 19 skull characters and 12 external body chcracrers from 32 adult specimens were conducted to examine morphological variation. Multiple regression analysis on the three species examined indicated that there were not sexually dimorphic in both skull and external body characters. Between these species examined showed a marked distinction, as detected by using discriminant function analysis, Specimens of Megaerops from Bali and Lombok were not morphologically distinct from M. kusnotoi, while our additional Sumatran Megaerops were morphologically similar to M. w. albicollis. This is the first report of M. kusnotoi from Bali and Lombok, and for M. w.albicollis from Sumatra.